Pembuatan Hardy Candy Mengunakan Ekstrak Buah Kersen (Muntingia calabura L.) Dan Ekstrak Buah Lemon (Citrus limon) - Siberani, Kiki Fatmala (Universitas Muhammadiyah Sumatera Utara, 2023)
Fruit series (Muntingia Calabura L) is a neotropic plant whose utilization has not Cherry fruit is a fruit whose existence we often encounter everywhere. Usually a lot of growing on the side of the road, wall cracks, yard, even in the gardens. This study aims to determine how to make hard candy and find out the extract of cherry (Muntingia calabura L) and lemon extract (citrus limon) and increase the usability of cherry fruit. The experimental design used was completely randomized design with two factors. The frist factor was Number of Cherry Extract (Muntingia calabura L.) (K) which consists of 4 levels, K1 = 10 ml, K2 = 13 ml, K3 = 16 ml, K4 = 19 ml and the second factor is the Amount of Lemon Extract (Citrus limon) (M) consisting of 4 levels, M1 = 0 ml, M2 = 5 ml, M3 = 10 ml, M4 = 15 ml. The amount of cherry extract gave a very significant effect (p 0.01) on the parameters of saccharose content, water content, antioxidant activity, organoleptic taste. While the texture organoleptic parameters give no significant effect (p 0.05). The amount of lemon extract gives a very significant effect (p 0.01) on the parameters of water content, antioxidant activity, organoleptic texture. While the parameters of saccharose content, water content and organoleptic taste did not have a significant effect (p 0.05).